Analysis of Stress Patterns in Coastal Women: Analisis Pola Stres pada Wanita Pesisir - Sari, Denita Permata; Hapsari, Widyaning; Iftayani, Itsna (Universitas Muhammadiyah Sidoarjo, 2025)
This study aims to analyze the stress patterns experienced by coastal women in Demanggedi Village, Purwodadi District, Purworejo Regency, focusing on the factors causing stress and the strategies they use to manage these pressures. The approach used in this study is qualitative with a descriptive method, where data were collected through in-depth interviews, non-participatory observation, and documentation. The results of the study indicate that coastal women experience stress influenced by uncertain weather, fluctuating prices of natural resources, and the dual burden of being housewives and breadwinners. Additionally, productive activities, such as processing sap into palm sugar and turning jeruju seeds into body scrub, not only help reduce stress but also provide additional income. This study highlights the importance of social support and community empowerment in reducing stress and improving the quality of life for coastal women. Highlights: Stress Factors – Coastal women face stress due to unpredictable weather, fluctuating natural resource prices, and dual responsibilities as homemakers and breadwinners. Coping Strategies – Engaging in productive activities like making palm sugar and body scrubs helps alleviate stress while generating additional income. Community Support – Social support and community empowerment play a crucial role in reducing stress and enhancing the well-being of coastal women. Keywords: Stress Patterns, Coastal Women, Mental Well-Being